ETIKA BISNIS PEDAGANG PADA JUAL BELI TELEPON GENGGAM BEKAS DITINJAU DARI PERSPEKTIF EKONOMI ISLAM - LALU MUH SHABIRAN; TITIEK HERWANTI (Maqdis: Jurnal Kajian Ekonomi Islam, 2017)
The theme of the article is "economy based on the principles of Islam". The purpose of this research is to know about business ethics former trader of mobile phones in Sub Selong East Lombok. This research was conducted with a qualitative approach. Focus of this study was to determine the merchant's business ethics on the sale and purchase of second hand phone in the District Selong East Lombok. Results of the study are: merchant opens on condition of used cell phones are sold, in taking high profits traders capitalize upon ignorance of the buyer, in getting a used cell phone from the merchant community push prices as low and sell at the highest possible price.